From dysbiosis to prediction: a novel gut microbiota–derived index for spontaneous bacterial peritonitis in HBV-related cirrhosis - Zhou, Zhewen; Sun, Xiu; Cheng, Danying; Xing, Huichun (Frontiers in Immunology, 2026)
ObjectiveSpontaneous bacterial peritonitis (SBP) is a severe complication of hepatitis B virus (HBV)-related cirrhosis, in which gut microbiota dysbiosis plays a pivotal role. This study aimed to characterize microbial alterations, establish a microbiota-derived index (SBP-MI), evaluate longitudinal changes, and develop an SBP risk prediction model (SBP-RP).MethodsA total of 135 participants were included: healthy controls (n=40), compensated cirrhosis (n=30), cirrhosis with ascites but without SBP (n=40), and SBP (n=25). Fecal 16S rRNA sequencing and clinical data were obtained. An additional 140 cirrhotic patients with ascites were prospectively followed for 6 months, with SBP occurrence as the endpoint; 40 provided paired fecal samples. SBP-MI was constructed from key microbial shifts, and multivariable Firth logistic regression identified independent predictors.ResultsSBP was characterized by enrichment of pathogenic taxa (Escherichia–Shigella, Klebsiella, Veillonella, Streptococcus) and depletion of short-chain fatty acid producers (Prevotella, Roseburia, Faecalibacterium, Bacteroides), forming the basis of SBP-MI. During follow-up, improved patients had greater microbial diversity and beneficial commensals, whereas progression was linked to Haemophilus expansion. SBP-MI effectively tracked these changes and outperformed the Hepatitis B Cirrhosis Dysbiosis Index. Multivariable analysis identified INR, previous history of SBP, and SBP-MI as independent predictors. The SBP-RP yielded an AUC of 0.91(95% CI: 0.82–0.99), with calibration that appeared acceptable in this cohort.ConclusionDistinct dysbiosis characterizes SBP. SBP-MI captures microbial imbalance and progression, while the SBP-RP model integrating microbial and clinical factors provides promising predictive value for early risk stratification.